Literasi Menulis Sekolah Dasar (Studi Kasus di SD Plus Rahmat Kota Kediri) - Ananta Sa'i Wijaya (Universitas Wijaya Kusuma Surabaya, 2023)
Research Purpose. The research conducted by the author aims to describe the stages of wiritng liletacy in SD Plus Rahmat Kediri. Methods. This study uses a qualitative method, with the type of case study research at the 4-6 grade level at SD Plus Rahmat Kota Kediri. The number of informants was 8 people consisting of teachers, students, librarians, and school principals using the purposive sampling technique. Data collection techniques are carried out by observation, Interview and Documentation. Data Analysis. The data analysis technique uses the concept of Miles and Huberman: Reduction, Presentation and Drawing Conclusions. Result and Discussion. The results of the study show that there are 3 stages in writing literacy, namely (1) the Habituation Stage, where students get used to resuming books they have read by writing the author's name, title, and contents. (2) Development Stage, availability of reading spots in the school environment. (3) Learning Stage, literacy classes are provided which are directly given by librarians who teach about writing.